Analisis Persediaan Jahe pada Produk Wedang Uwuh di UMKM Weeka Sejahtera Group Kabupaten Bantul - Kartika, Dwi; Permai, Ni Made Suyastiri Yani (Journal of Agricultural Social and Business, 2025)
UMKM Weeka Sejahtera Group is a herbal drink business with wedang uwuh original as the best-selling product. The highest composition of wedang uwuh is ginger; however, it is constrained by supply from suppliers, so proper inventory management is needed for smooth production. This study aims to analyze the optimal ordering, safety stock and reorder point of ginger needs for wedang uwuh production at UMKM Weeka Sejahtera Group. This research uses a quantitative approach with descriptive research. The research implementation method employs a case study approach. The data analysis methods applied include EOQ (Economic Order Quantity) analysis, safety stock and reorder point. The results of the analysis of ginger inventory in wedang uwuh products at UMKM Weeka Sejahtera Group are not optimal, as there is a discrepancy between the optimal ordering of ginger and the actual ordering of ginger, which is 69.58 kg; safety stock of 74.22 kg;and reorder point of 131 kg.